IMPROVING WORK PERFORMANCE WITH THE INFLUENCE OF ROTATION THROUGH WORK ENTHUSIASM AND MOTIVATION IN THE HOUSING, RESIDENTIAL AND DEFENSE AREA SERVICES OF BULELENG REGENCY - Ningsih, Luh Kartika; Gorda, A. A. Ngurah Eddy Supriyadinata; Dewi, Komang Trisna Sari; Budiarta, I Made Agus; Yasa, Kadek Tirta (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the increase in work performance with the influence of rotation through work enthusiasm and motivation in the housing, settlement and defense areas of Buleleng Regency. The population and sample in this study were 92 employees at the Housing, Settlement and Defense Areas Office of Buleleng Regency. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on variance SEM, which is well known as Partial Least Square (PLS) visual version 3.0. The results of this study indicate that rotation has a direct influence on morale at the Housing, Settlement and Defense Areas Services in Buleleng Regency. Rotation has a direct influence on motivation in the Housing, Residential Areas and Defense Services of Buleleng Regency. Rotation has a direct influence on work performance at the Housing, Settlement and Defense Areas Office of Buleleng Regency. Morale has a direct influence on work performance at the Housing, Settlement and Defense Areas Office of Buleleng Regency. Motivation has a direct influence on work performance at the Housing, Settlement and Defense Areas Office of Buleleng Regency. Rotation has a direct influence on work performance with work enthusiasm as an intervening variable at the Housing, Residential and Defense Areas Office of Buleleng Regency. Rotation has a direct influence on work performance with motivation as an intervening variable at the Housing, Residential and Defense Areas Office of Buleleng Regency.